UMA LEITURA DAS FALAS DE ALUNOS DA EDUCAÇÃO BÁSICA A RESPEITO DE AVALIAÇÕES EM SALA DE AULA DE MATEMÁTICA - LUIZA CORDEIRO DE ANDRADE FAUSTINO (2023)
ABSTRACT This work aimed to investigate meanings produced by basic education students, in an interview context, about the evaluation processes in mathematics classrooms. The research is qualitative and the main theoretical-methodological framework is the Model of Semantic Fields (MSF). We present some discussions about the evaluation in classrooms, in dialogues with works that focus on students. The main questions in an attempt to read the meanings produced that move us are: How do the students feel the evaluation? How to they handle them? What are the affective, political and pedagogical crossings that happen to these students? Interviews were carried out with students in public schools in the municipality of Aquidauana, Mato Grosso do Sul State, and these were recorded in audio and video. Our analysis were made from students’ speeches regarding to school, mathematics evaluations and the mathematics classes, face-to-face and in remote teaching. We analyzed the drawings they produced during the interviews and their relationship with their ways of handling scholar evaluation in classroom of mathematics classes. Fear, anguish and sadness are emotions present in students’ speeches and drawings. Isolation and few directions for carrying out the activities in remote teaching are also part of the meanings produced by them. Our work produces a political discussion of scholar evaluation in the direction of operating in the affective dimensions of students’ speeches regarding scholar evaluations. Keywords: Scholar Evaluation. Mathematics. Students. Drawings. Affections. Remote Teaching. Model of Semantic Fields.